Pengenalan Dasar-Dasar Komputer di SD Inpres 12/79 Bonepute - Fitri, Fitriani; Andi Tabrani, Andi Tabrani Rasyd; Ninda Julfikarni, Ninda Julfikarni; Yuniar S., Yuniar S.; Nur Syafina, Nur Syafina; Jumria, Jumria; Syahrul Arifin, Syahrul Arifin; Aldi, Aldi; Andi Zulhuzaemy, Andi Zulhuzaemy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the implementation of basic computer introduction activities in improving digital literacy among students of SD Inpres 12/79 Bonepute. The research method used is a case study with a qualitative approach. Data collection techniques were carried out through interviews, documentation, and limited observation of basic computer learning activities. The researcher applied data analysis procedures consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the basic computer introduction activities at SD Inpres 12/79 Bonepute were implemented through several programs, namely: 1. introducing computer hardware and its functions, 2. introducing basic software such as operating systems and Microsoft Word, 3. introducing a brief history of computer development, and 4. hands-on practice using computers for simple typing activities. The implementation of this program has had a positive impact on improving students' technological skills, as they have begun to get accustomed to using computers as a learning tool, gained a basic understanding of computer functions, and shown high enthusiasm in utilizing technology as part of the learning process.